Pengembangan Media Pembelajaran KOMIKA (Komik IPAS) sebagai Bentuk Literasi Sains pada Materi Perubahan Wujud Benda di Sekolah Dasar - Rizky, Amalia Suryani; Faradita, Meirza Nanda; Afiani, Kunti Dian Ayu (Jurnal Simki Pedagogia, 2025)
The purpose of this study was to create a KOMIKAS (IPAS Comic) media product by applying the criteria of validity, practicality, and effectiveness. This study used five stages of the ADDIE model development method, namely analysis, design, development, implementation, and evaluation. The subjects of this study were 22 fourth-grade students at SDN Putat Jaya II Surabaya. The study was conducted from November 2024 to January 2025. The data collection methods used were tests and questionnaires. The research instruments used were test sheets, teacher response questionnaires, student questionnaires, and expert and material validation sheets. Based on the results of the study, the KOMIKA (IPAS Comic) media met the requirements of being very valid with a media expert validation percentage of 87% and a material expert validation percentage of 92%. Students obtained a percentage of 83% in the very practical category, while teachers obtained a percentage of 91% on the practicality questionnaire response sheet. Based on the level of student learning completion, the effectiveness test obtained a score of 91% with the "effective" category. The KOMIKA media product (IPAS Comic) meets the requirements of validity, usability, and efficacy.